Critical Islam and the Muslim Crisis: Z. Sardar’s Double Critique of Western Modernity and Muslim Orthodoxy - Belhaj, Abdessamad (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2025)
Critical Islam is a Muslim discourse that fundamentally questions contemporary Muslim societies, traditions, and cultures in response to the crisis in Muslim societies, amidst the rise in violence, authoritarianism, and foreign military interventions. This school of thought represents a new development in Islamic thought and an attempt to overcome the problems posed by tradition and modernity. This article examined the British-Pakistani intellectual Ziauddin Sardar’s views of critical Islam. My approach, which is based on intellectual history, places his arguments and theses in the context of the intellectual networks in which they originated as well as the developments that have taken place in the Muslim world over the last two centuries. One of the main findings, underlined here, is that Sardar offers an innovative and dual critique of the West and the Muslim tradition from an ethical and epistemic perspective. Additionally, the goal of his critical Islam is to change, pluralize, and end violence in the Muslim world. However, Sardar’s project is elitist and lacks spiritual appeal for the great majority of Muslims. Therefore, it should be interpreted as an intellectual critical engagement with Islam and the West that emphasizes personal emancipation.